Semantic Error Analysis of Active - Passive Sentences in the Translation of Al Jawahiru Al Kalamiatu by Thahir Bin Saleh Al Jazair - Rofiqoh, Nihayatur; Mubarok, Zacky Mubarok; Darsita, Darsita Suparno; Ahmad, Ahmad Hifni; Ulil, Ulil Abshar (Institut Agama Islam Negeri Metro, 2025)
This research aims to describe the semantic error analysis of active-passive sentences and the difference between the two sentences in the translated book of Al-Jawahiru Al-Kalamiatu by referring to several books related to the issue. The method used in this research is literature study. In this study, researchers attempted to collect data by reading the text of the translated book of Al Jawahiru Al Kalamiatu, with the aim of obtaining messages, information, including the content to be conveyed by the author through the medium of written words / language. In the next stage, the researchers categorized active and passive sentences in Arabic and Indonesian. After that, the researcher analyzed semantic errors in active-passive sentences, then corrected the translation of mabni malum and mabni majhul in passive sentences and active sentences in the translation book of Al Jawahiru Al Kalamiatu. The results show that there are some mabni malum which when translated are more oriented towards passive sentences, and vice versa there are mabni majhul which when translated are more oriented towards active sentences but in the sentence the subject still plays a role like an active-passive sentence. This happens because mabni malum-majhul is more oriented to the form of the word while the active-passive sentence is on the meaning of the word. In the translation of this book, there are still many mistakes that need to be studied again such as the number of filiyah, the number of ismiyah or syntactic and morphological aspects. Therefore, further research needs to be done in order to facilitate us, especially as students, in understanding the structure of differences and similarities between B1 and B2, as well as the meaning of the contents of the book.